Preparation and Characterization of Chitosan-Graft-Polyacrylamide and its Application in Wastewater Treatment - Zheng, H.L.; Zhang, P.; Zhu, G.C.; He, Q.; Zhang, Z.Q. (Asian Journal of Chemistry, 2012)
Graft copolymerization of acrylamide over chitosan has been performed. The effect of reaction variables such as type and dosage of the initiator, total concentration of the reactants, reactants ratio, nitrogen blowing time, temperature and reaction time were investigated. The orthogonal experiment indicated that the most important factor was the ratio of reactor, next the concentration of the initiator and lastly was reaction temperature. The flocculants were detected and characterized with IR spectroscopy and scanning electron microscope. The adsorption capacity for removal of Cu(II) and Cr(VI) were up to 96.31 % and 84.17 %, respectively.